"For Thee America! For Thee Syria?": Alexander Maloof, Orientalist Music, and the Politics of the Syrian Mahjar. Issue 4 (November 2020) - BOTHWELL, BEAU
Abstract: In 1894 Syrian émigré Alexander Maloof arrived in the United States to join the thriving community in New York's "Syrian Quarter." Working first as a music instructor and pianist, Maloof found success as a bandleader, composer, arranger, and publisher, integrating Arabic and US popular music and light classical styles. He wrote and edited Arabic-language piano songbooks for the Arabophone communities in the United States, and ran the Maloof Records label, the "Oriental" division of the Gennett Company's "race records" enterprise. Drawing on Arabic-language discourse from around the Syrian mahjar (diaspora), this article uses Maloof's output to demonstrate music's role in the vibrant and contested political conversations taking place in Arabic around the world, from the homelands around Beirut and Damascus, to the initial Syrian settlements in Cairo and Paris, to the American colonies in Sao Paulo, Buenos Aires and New York. Concluding with a discussion of the 1919 "American Maid" (composed under a pseudonym), I argue that a thorough understanding of the history of Orientalist popular music in the Americas requires a decentering of European American audiences in order to examine those questions animating the New York mahjar, most centrally the political fate of greater Syria.